Clinical and pathogenetic significance of tetanus toxin. Clinical сase - G.O. Revenko; V.V. Mavrutenkov (Zaslavsky O.Yu., 2017)
Tetanus is a serious, potentially life-threatening infectious disease, occurrence of which is limited to post-vaccination immunity and develops as a result of Clostridium tetani spores penetration into the wound. This pathogen produces one of the strongest toxins, tetanospasmin, that causes clinical manifestations. The most common symptoms are lockjaw, dysphagia, sardonic smile and tetanic seizures with tonic tension of the muscles. Death usually occurs as a result of respiratory or cardiac failure. Treatment is usually performed in the intensive care departments to avoid development of potential complications that are life-threatening. This article clearly shows the clinical case of tetanus in unvaccinated 6-year-old child with favorable outcome. The disease duration was 64 days. Targeting primary care physicians to provide immunization to risk groups will help to prevent tetanus.